Collection policy(s) in puppet theater in Portugal today (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
The article describes several modalities of conservation and preservation of the collection of puppet theater companies. From the description of case studies that belong to the theatrical repertoire active in Portugal today, we can identify common traits that aim to value both ancient and contemporary assets. The old or traditional puppet is treated as an object of identity memory, valued as a material and immaterial heritage, and is also safeguarded as a scenic and museological objects. Contemporary collections are marked by a new perception of the puppet as an aesthetic and artistic object, and are exhibited or reused in community outreach activities.
Keywords: collection; pupettry; memory; heritage; museum